CX3CR1‐Expressing Myeloid Cells Regulate Host–Helminth Interaction and Lung Inflammation (Adv. Biology 3/2022). Issue 3 (18th March 2022) - Kim, Sang Yong; Barnes, Mark A.; Sureshchandra, Suhas; Menicucci, Andrea R.; Patel, Jay J.; Messaoudi, Ilhem; Nair, Meera G.
Abstract : Chemokine Receptor CX3CR1 Tissue‐migrating parasitic worms trigger immune effector cells that migrate to the worm to trap and kill it. In article 2101078, Nair and co‐workers investigate lung eosinophils (red) and myeloid cells (green) and their interaction with the parasitic worm using a combination of reporter transgenic mice and mice deficient in the chemokine receptor CX3CR1.